مساهمة المسؤولية الاجتماعية في تحسين جودة حياة العمل في المؤسسة الاقتصادية " دراسة تحليلية من وجهة نظر العاملين بمؤسسة الاسمنت ولاية قسنطينة " - بوغليطة, إلهام; مهري, عبد المالك; زياني, خولة (University of Eloued جامعة الوادي, 2018)
تهدف الدراسة إلى تبيان مدى مساهمة المسؤولية الاجتماعية في تحسين جودة حياة العمل من وجهة نظر العاملين، ووقع اختيارنا على مؤسسة الإسمنت لولاية قسنطينة كعينة لتطبيق هذه الدراسة، حيث تم توزيع 68 استمارة استبيان على العاملين بالمؤسسة، ولاختبار فرضيات الدراسة تم استعمال مجموعة من الأساليب الإحصائية، كالمتوسط الحسابي والانحراف المعياري واختبار Tللعينة الواحدة للوصول إلى نتائج تساعدنا في الحكم على المؤسسة، ومن أهم النتائج التي توصلت لها الدراسة نذكر: - لا تساهم المسؤولية الاجتماعية في تحسين نوعية حياة العمل من وجهة نظر العاملين في مؤسسة الاسمنت بولاية قسنطينة. - تساهم المسؤولية الاجتماعية بدرجة متوسطة في تحسين ظروف وتنظيم العمل للعاملين في المؤسسة محل الدراسة. - لاتساهم المسؤولية الاجتماعية مساهمة فعالة في تحسين الصحة والسلامة المهنية للعاملين في المؤسسة محل الدراسة. -لا تساهم المسؤولية الاجتماعية مساهمة فعالة في تحسين الخدمات الاجتماعية للعاملين في المؤسسة محل الدراسة. -تساهم المسؤولية الاجتماعية بدرجة متوسطة في تحسين حقوق العاملين في المؤسسة محل الدراسة. Abstract: : The study aims to show the contribution of social responsibility in improving the quality of work life from the perspective of the two years. The foundation was selected by Constantine Cement Foundation as a sample for the implementation of this study. In order to test the hypotheses of the study, a number of statistical methods were used, such as arithmetic mean, standard deviation and T test for the sample to reach results that help us to judge the institution. The most important findings of the study are:- Social responsibility does not contribute to improving the quality of working life from the point of view of workers in the Cement Corporation in Constantine - Social responsibility contributes moderately to improving the conditions and organization of work for the workers in the institution in question. - Social responsibility does not contribute effectively to improving the occupational health and safety of the workers in the institution in question. Social responsibility does not contribute effectively to improving the social services of the employees of the institution in question. - Social responsibility contributes moderately to improving the rights of employees in the institution in question
The contribution of social responsibility in improving the quality of working life in the economic institution "An analytical study from the point of view of workers in the Cement Corporation of Constantine
مجلة رؤى المجلد الثامن العدد الأول
Keywords: المسؤولية الاجتماعية، العمال، جودة حياة العمل، الصحة المهنية، الخدمات الاجتماعية.; social responsibility, workers, quality of work life, occupational health, social services. Jel Classification Codes : M10, M12